Final instar larva of Acanthagrion truncatum Selys, 1876 (Zygoptera: Coenagrionidae) - Vilela, Diogo Silva; Venâncio, Henrique; Santos, Jean Carlos (Zootaxa, 2020)
Here we describe the final instar larvae of Acanthagrion truncatum Selys, 1876, the 16th described for the genus. We compare the diagnostic characters of A. truncatum with other species of the Group II. Although very similar to other Acanthagrion, the larvae of A. truncatum can be separated from other congeners from having the following character combination: cephalic lobes bulging and rounded, seven antennomeres, 2+1 or 2 premental setae, and nodus at 0.60–0.62 of total length of the lamella.